INTERPERSONAL INTELLIGENCE AMONG 4–5 YEAR-OLDS IN BANTEN PROVINCE: THE ROLE OF NUTRITION AND MENTAL HEALTH - Suwardi, Fitri Laila; Susanti, Debie (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
The purpose of this article is to examine the relationship between children's diet and their social and emotional well-being in Banten Province, focusing on kids aged four to five. This definitive study employed a methodology known as causality research. Interpersonal intelligence (Y) served as the dependent variable, while dietary intake (X1) and psychological well-being (X2) served as the independent variables. The participants or subjects of this study are all PAUD teachers in Pandeglang Regency, Banten Province, whether they are employed in a formal or informal setting. include the 1,469 teachers working in preschools, daycares, and kindergartens. For this study, we used multistage cluster random sampling to collect data from the minimum number of participants required by the Slovin formula (n=94). According to the findings, children's nutritional status significantly affects their interpersonal intelligence development, mental health significantly influences children's interpersonal intelligence development, and both factors significantly affect children's interpersonal intelligence development. An adjusted R2 score of 0.808 indicates that the relationship between children's nutritional state and mental health and their interpersonal IQ is robust.